Ectopic pregnancy at Soavinandriana hospital center, Antananarivo, Madagascar - Randriamahavonjy, Romuald; Rabarikoto, Hary F.; Mahefarisoa, Fy N. A. T.; Ratsiatosika, Tanjona A.; Andrianampanalinarivo, Hery R. (International Journal of Research in Medical Sciences, 2018)
Background: In the first trimester pregnancy, ectopic pregnancy is the most life-threatening gynecological emergency. The aim of this study was to estimate the epidemiological, diagnostic and therapeutic aspects of ectopic pregnancy in Antananarivo, Soavinandriana Hospital Center. Methods: This was a prospective study carried out among consecutive patients of ectopic pregnancy admitted from January 2014 to February 2016. All cases of diagnosed ectopic pregnancy admitted and managed in the gynecological ward were included in the study. These were reviewed and information was extracted regarding women characteristics, clinical features, diagnosis, management and post-operative complications. Results: During this period, there were 41 ectopic pregnancies. The incidence was therefore 20/1000 births. The mean age was 32,26years. The peak age of incidence was the 30-39 years age group. Nulliparous were the most sufferers. The commonest risk factors identified were previous genital infection. (n=17; 41,46%) previous induced abortions (n=15; 36,58%) and the age ≥35 years old (n =16; 39,02%). Twenty seven patients (n=11) did not have a quantitative measurement of the β subunit of human chorionic gonadotropin (β-hCG). Pelvic ultrasound (transabdominal) was performed on all patients. The majority of patients had a laparotomy (n=35, 85,36%). Tubal pregnancies were noted in 90% (n=37) cases. Conclusions: Health educations on early presentation in hospitals are expected to reduce the incidence of EP and the consequent loss of reproductive potential. The majority of risk factors we identified can be early detected and treated.